Effects of valganciclovir on spermatogenesis in renal transplant patients – results of a multicenter prospective nonrandomized study. (6th January 2020) - McLeroth, Patrick; Paduch, Darius A.; Abt, Markus; Hughes, Richard; Moore, Suzanne; Mudie, Nadejda
Summary: Ganciclovir (GCV) inhibits spermatogenesis in preclinical studies but long‐term effects on fertility in renal transplant patients are unknown. In a prospective, multicenter, open‐label, nonrandomized study, male patients were assigned to Cohort A [valganciclovir (VGCV), a prodrug of GCV] ( n = 38) or B (no VGCV) ( n = 21) by cytomegalovirus prophylaxis requirement. Changes in semen parameters and DNA fragmentation were assessed via a mixed‐effects linear regression model accounting for baseline differences. Sperm concentration increased post‐transplant, but between baseline and treatment end (mean 164 days Cohort A, 211 days Cohort B), the model‐based change was lower in Cohort A (difference: 43.82 × 10 6 /ml; P = 0.0038). Post‐treatment, sperm concentration increased in Cohort A so that by end of follow‐up (6 months post‐treatment) changes were comparable between cohorts (difference: 2.09 × 10 6 /ml; P = 0.92). Most patients' sperm concentration improved by end of follow‐up; none with normal baseline concentrations (≥20 × 10 6 /ml) were abnormal at end of follow‐up. Changes in seminal volume, sperm motility/morphology, DNA fragmentation, and hormone levels were comparable between cohorts at end of follow‐up. Improvement in semen parameters after renal transplant was delayed in men receiving VCGV, but 6 months post‐treatment parameters were comparable between cohorts.